Independent origin of the anterior descending and circumflex arteries in the left valsalva sinus by coronary angiography - Guillermo Rivera-Cardona (Revista de la Facultad de Ciencias de la Salud, 2013)
Congenital coronary artery anomalies are detected in about 0,8 – 3% of patients undergoing coronary angiography. The study describes a case report about a woman of 87 years old; it´s performed coronary angiography and determined a descending anterior and circumflex arteries originated in the ascending aorta artery in independent ostium. The clinical importance in the anatomical variations of the coronary arteries and their branches are the possible relationships with ischemia, myocardium infarct and death, however some patients are asymptomatic and the diagnostic is postmortem.